Highlighting the Strategic Value of Green Process Innovation in the Basic Materials Sector - Nanda Atika Sari; Alfonsa Dian Sumarna (Master of Management, School of Business and Management, Petra Christian University, 2025)
As awareness of environmental and social issues increases, responsible business practices, such as green accounting, Corporate Social Responsibility (CSR) disclosure, and green process innovation, are increasingly recognized for their role in creating long-term value. This study aims to empirically examine the impact of three sustainability initiatives (green accounting, CSR disclosure, and green process innovation) on company profitability in the basic materials sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. Green accounting and CSR disclosure have not been proven to have a significant impact on company profitability. However, different findings were found for green process innovation, which showed a positive and significant effect on profitability. This implies that companies' efforts to integrate innovative practices that reduce environmental impacts into their operational processes tend to correlate with improved financial performance. Green process innovation has been empirically proven to have a positive influence, as it can serve as a source of competitive advantage that is difficult to imitate (inimitable), thereby driving profitability. Companies should allocate more resources to developing green process innovations, such as energy efficiency, waste recycling, and low-emission technologies. Investments in R&D and collaborations with third parties can be effective strategies for accelerating innovation.